Absence of circular polarisation in reflections of butterfly wing scales with chiral Gyroid structure - Saba, Matthias; Wilts, Bodo D.; Hielscher, Johannes; Schröder-Turk, Gerd (Materials Today, 2014)
The single Gyroid, a triply-periodic ordered chiral network of cubic symmetry, appears as a nanostructure in the green-colored wing scales of various butterflies. In lossless and perfectly ordered single Gyroid materials, the structural chirality leads to circularly polarized reflections from crystals oriented in the [100] direction. Here we report a circular polarisation study of the macroscopic reflections of the wing scales of Callophrys rubi and Teinopalpus imperialis that reveals no circular dichroism, that is, we find no significant difference in the reflectance values for left- and right-circularly polarized light. The reasons for the absence of circularly polarized reflections is likely to be a compound effect of various factors, including crystallite orientation, presence of both leftand right-handed single Gyroid enantiomers, and structural disorder. Each of these factors weakens, but does not fully extinguish, the circular polarisation signal. We further find a substantial amount of blue-absorbing pigment in those wing scales of C. rubi that are structured according to the single Gyroid. Numerical simulations demonstrate that absorption, while evidently reducing overall reflectance, does generally not reduce the circular dichroism strength. The experimental findings of this paper, however, clearly demonstrate that circular dichroism is absent from the reflections of the butterfly wing scale. Henceforth, the chiro-optical response of the idealised structure does not fulfil a biological photonic function.
EAM Import::2019-03-13

A Chiral Beamsplitter Inspired by Butterfly Nanostructures - Turner, Mark D.; Saba, Matthias; Zhang, Qiming; Cumming, Benjamin P.; Schröder-Turk, Gerd; Gu, Min (Frontiers in Optics 2013, 2013)
Here we present a chiral analog of the linearly polarizing beamsplitter. This microscopic device was built from a biomimetic chiral photonic crystal and separates left and right-handed circularly polarized light at near-infrared wavelengths.
EAM Import::2019-03-13

Chiral Photonic Crystals with 4-fold Symmetry: Band Structure and S-Parameters of Eight-Fold Intergrown Gyroid Nets - Saba, Matthias; Turner, Mark D.; Gu, Min; Mecke, Klaus; Schröder-Turk, Gerd (Proceedings of SPIE, 2013)
The Single Gyroid, or srs, nanostructure has attracted interest as a circular-polarisation sensitive photonic material. We develop a group theoretical and scattering matrix method, applicable to any photonic crystal with symmetry I432, to demonstrate the remarkable chiral-optical properties of a generalised structure called 8-srs, obtained by intergrowth of eight equal-handed srs nets. Exploiting the presence of four-fold rotations, Bloch modes corresponding to the irreducible representations E- and E+ are identified as the sole and non-interacting transmission channels for right- and left-circularly polarised light, respectively. For plane waves incident on a finite slab of the 8-srs, the reflection rates for both circular polarisations are identical for all frequencies and transmission rates are identical up to a critical frequency below which scattering in the far field is restricted to zero grating order. Simulations show the optical activity of the lossless dielectric 8-srs to be large, comparable to metallic metamaterials, demonstrating its potential as a nanofabricated photonic material.
EAM Import::2019-03-13

Circular Dichroism in Biological Photonic Crystals and Cubic Chiral Nets - Saba, Matthias; Thiel, M.; Turner, M. D.; Hyde, S. T.; Gu, Min; Grosse-Brauckmann, K.; Neshev, D. N.; Mecke, Klaus; Schröder-Turk, Gerd (Physical Review Letters, 2011)
Nature provides impressive examples of chiral photonic crystals, with the notable example of the cubic so-called srs network (the label for the chiral degree-three network modeled on SrSi2) or gyroid structure realized in wing scales of several butterfly species. By a circular polarization analysis of the band structure of such networks, we demonstrate strong circular dichroism effects: The butterfly srs microstructure, of cubic I4(1)32 symmetry, shows significant circular dichroism for blue to ultraviolet light, that warrants a search for biological receptors sensitive to circular polarization. A derived synthetic structure based on four like-handed silicon srs nets exhibits a large circular polarization stop band of a width exceeding 30%. These findings offer design principles for chiral photonic devices.

Group theory of circular-polarization effects in chiral photonic crystals with four-fold rotation axes applied to the eight-fold intergrowth of gyroid nets - Saba, Matthias; Turner, Mark D.; Mecke, Klaus; Gu, Min; Schröder-Turk, Gerd (Physical Review B, 2013)
We use group or representation theory and scattering matrix calculations to derive analytical results for the band structure topology and the scattering parameters, applicable to any chiral photonic crystal with body-centered-cubic symmetry I432 for circularly polarized incident light. We demonstrate in particular that all bands along the cubic [100] direction can be identified with the irreducible representations E-+/-, A, and B of the C-4 point group. E+ and E- modes represent the only transmission channels for plane waves with wave vector along the Delta line, and E- and E+ are identified as noninteracting transmission channels for right-and left-circularly polarized light, respectively. Scattering matrix calculations provide explicit relationships for the transmission and reflectance amplitudes through a finite slab which guarantee equal transmission rates for both polarizations and vanishing ellipticity below a critical frequency, yet allowing for finite rotation of the polarization plane. All results are verified numerically for the so-called 8-srs geometry, consisting of eight interwoven equal-handed dielectric gyroid networks embedded in air. The combination of vanishing losses, vanishing ellipticity, near-perfect transmission, and optical activity comparable to that of metallic metamaterials makes this geometry an attractive design for nanofabricated photonic materials.

Miniature chiral beamsplitter based on gyroid photonic crystals - Turner, Mark D.; Saba, Matthias; Zhang, Qiming; Cumming, Benjamin P.; Schröder-Turk, Gerd; Gu, Min (Nature Photonics, 2013)
The linearly polarizing beamsplitter is a widely used optical component in photonics. It is typically built from a linearly birefringent crystal such as calcite, which has different critical reflection angles for s- and p-polarized light, leading to the transmission of one linear polarization and angled reflection of the other. However, the analogue for splitting circularly polarized light has yet to be demonstrated due to a lack of natural materials with sufficient circular birefringence. Here, we present a nano-engineered photonic-crystal chiral beamsplitter that fulfils this task. It consists of a prism featuring a nanoscale chiral gyroid network and can separate left- and right-handed circularly polarized light in the wavelength region around 1.615 µm. The structure is fabricated using a galvo-dithered direct laser writing method and could become a useful component for developing integrated photonic circuits that provide a new form of polarization control.
EAM Import::2019-03-12